SONIC ENVIRONMENT MODELING BASED ON ACTIVITIES IN URBAN OPEN PUBLIC SPACES USING SOUNDSCAPE SIMULATOR - Salim, Helga
This research aims to study the relationship between sonic environment condition and occurrence of activities in urban open public spaces. This research is done by using soundscape simulator equipment which involves 51 student participants. Participants make a sonic environment composition based on four activities (reading, relaxation, talking, and playing with children). The composition which is produced is assessed by every composer based on 3 perception dimensions that are the comfort, dynamics, and communication. The compositions which are made show that there are sound sources that are suitable for reading, relaxation, talking, and playing with children activities. The composition data which is processed with hierarchical cluster analysis based on perception and sound sources shows that activities in urban open public spaces can be divided into two: individual activities (reading and relaxation) and social activities (talking and playing with children). Based on perception dimension assessment by participants, individual activities need a simple and private environment while social activities need varied and communal environment. Both activities need sonic environment condition, which is the comfort, especially for individual activities. Two sonic environment model in open public spaces are successfully built by using the logistic regression method. The first model correlates the activity with the sound pressure level of the sound source while the second model correlates the activity with the perception dimension. Each of those models has the prediction accuracy level in the mount of 92% and 84%.